Investigating the Variation in Leaf Traits Within the Allium prattii C.H. Wright Population and Its Environmental Adaptations - Shuai-Shuai Zhang; Zi-Jun Tang; Kun Chen; Xiao-Jing Ma; Song-Dong Zhou; Xing-Jin He; Deng-Feng Xie (Plants)
Morphological and micro-morphological traits of characteristics serve as the cornerstone for species identification and taxonomy, and they also ensure the adaptive responses of species to specific environmental conditions. Allium prattii C.H. Wright is mainly distributed in the mountains of southwestern China (MSC) and adjacent regions, and exhibits pronounced variations in leaf morphology and micro-morphology across different growth environments, making it an ideal taxa to study species adaptation to diverse conditions. In this study, we conducted extensive field surveys, sample collections, and morphological experiments, amassing data on leaf morphological and micro-morphological traits from 45 populations of A. prattii. Specifically, we explored the differences in leaf morphology among populations and the patterns of geographical distribution. Consequently, we examined the correlation between seven climatic factors, longitude, latitude, and leaf morphological traits, and simulated the changes in the A. prattii distribution area during different historical periods. Our results indicate that all populations of A. prattii can be categorized into four distinct lineages, characterized by significant leaf morphological divergence and distinct geographical distribution patterns. Populations located in the Hengduan Mountains and neighboring regions demonstrated elevated coefficients of variation (CV) in leaf morphology. The correlation analysis between morphological traits and climatic factors highlighted substantial links between the density of stomata on the upper epidermis and environmental variables, as well as significant correlations between leaf length/width and geographical distribution (latitude and longitude). Simulations of the distribution area revealed that the distribution ranges of A. prattii underwent a significant fluctuation from the Last Interglacial Period (LIG) to the Last Glacial Maximum (LGM), the Mid-Holocene (MH), and the current period, accompanied by expansion of its potential distribution area in the future. These results underscore that the leaf morphology of A. prattii has significantly varied in response to climatic environmental factors across different regions, with a decrease in leaf width and an increase in stomatal density on the upper epidermis. The heterogeneous environment of the southwestern mountain region, characterized by variations in altitude, temperature, and precipitation, is the primary driver of morphological variation and geographical distribution patterns in A. prattii leaves. Our findings hold substantial scientific significance, shedding light on the evolutionary adaptation of species in the MSC and adjacent areas.